Characteristics of the development of the explosive strenght and agility in young basketball - Nikolic, D.; Kocic, M.; Bojic, I.; Velickovic, M.; Beric, D. (FIS communications in Physical Education, Sport and Recreation, 2016)
Basketball is a sport that consists of short but very intense activities, interrupted by longer or shorter periods of passive or active rest, during which the basketball player recovers. Vertical jumps, which require an appropriate level of explosive strength are of great importance for success in basketball and are manifested in situations such as jump shot and jump towards the ball. Agility is a motor ability which is also important for basketball. Motor structures of this type are very common in the game because, due to changes of the situations, the players are required to start quickly, to run fast and change the direction, as well as to stop quickly. The aim of this study was to determine the differences in the explosive strength and agility between younger pioneers, pioneers, cadets and juniors and identify where that difference is greatest, in order to recognize the period when the development of the mentioned skills is greatest. The sample in this study consisted of 89 basketball players of basketball clubs: YBC "Constantine" from Nis, YBC "Junior" from Nis and BC "Ma.inac" from Kraljevo. The respondents were of various ages: younger pioneers (n = 21), pioneers (n = 27), cadets (n = 22) and juniors (n = 19). The respondents were in the basketball training process for at least three years. For the assessment of the explosive leg power of the basketball players, two tests were used: jump from the squat (Squat jump) - SJ and jump from the squat with the preparation (Countermovement Jump) - CMJ. To assess the agility of the basketball players, two tests were used: Agility T Test - ATT and Hexagon Agility Test- HAT. The data analysis was performed with the help of One-factor analysis of variance- ANOVA. Th results showed that there were significant differences in the tested abilities between younger pioneers and pioneers, as well as between the pioneers and cadets, but not between cadets and juniors. The results also show that the development of the mentioned capabilities is largest in the transition from the pioneer in the cadet age.